Public-private alliances for sustainable commodity supply chains: Opportunities and risks in the South African mining sector - Melanie Müller; Christina Saulich; Meike Schulze (Stiftung Wissenschaft und Politik (SWP), 2022)
The promotion of public-private cooperation in resource-rich countries of the Global South can serve as a flanking measure that strengthens the impact of supply chain laws. The case of the South African mining sector in its struggle against Covid-19 shows that close cooperation between companies, the state and private organisations can, under certain conditions, increase the sustainability of transnational supply chains. Nevertheless, these types of alliances carry the risk of negative cascading effects if core state tasks are delegated to companies. The German government should therefore take into account the public regulatory landscape in the mining sector, particularly the quality of the implementation of laws in partner countries, and initiate measures that can work to strengthen social and environmental rights.
Keywords: 330